The cryopreservation process induces alterations in proteins associated with bull sperm quality: The equilibration process could be a probable critical control point - Arunkumar, Ramasamy; Kumaresan, Arumugam; Sinha, Manish Kumar; Elango, Kamaraj; Ebenezer Samuel King, John Peter; Nag, Pradeep; Karuthadurai, Thirumalaisamy; Baithalu, Rubina Kumari; Mohanty, Tushar Kumar; Kumar, Rakesh; Datta, Tirtha Kumar (Frontiers in Endocrinology, 2022)
The present study quantitatively characterized the proteomic changes in bull spermatozoa induced by cryopreservation process. We performed high-throughput comparative global proteomic profiling of freshly ejaculated (before cryopreservation), equilibrated (refrigerated storage; during cryopreservation) and frozen (ultra-low temperature; after cryopreservation) bull spermatozoa. Using liquid chromatography- mass spectrometry (LC-MS/MS) technique, a total of 1692, 1415 and 1286 proteins were identified in fresh, equilibrated and cryopreserved spermatozoa, respectively. When the proteome of fresh spermatozoa was compared with equilibrated spermatozoa, we found that 166 proteins were differentially expressed. When equilibrated spermatozoa was compared with cryopreserved spermatozoa, we found that 147 proteins were differentially expressed between them. Similarly, we found that 156 proteins were differentially expressed between fresh and cryopreserved spermatozoa. Among these proteins, the abundance of 105 proteins were lowered during the equilibration process itself while the abundance of 43 proteins were lowered during ultralow temperature preservation. Remarkably, the equilibration process lowered the abundance of sperm proteins involved in energy metabolism, structural integrity and DNA repair, and increased the abundance of proteins associated with proteolysis and protein degradation. The abundance of sperm proteins associated with metabolism, cGMP-PKG (Cyclic guanosine 3',5'-monophosphate-dependent protein kinase G) signalling and regulation of actin cytoskeleton were also altered during the equilibration process. Collectively, the present study showed that the equilibration step in the bull sperm cryopreservation process was the critical point for sperm proteome, during which a majority of proteomic alterations in sperm occurred. These findings are valuable for developing efficient protocols to minimise the protein damage and to improve the quality and fertility of cryopreserved bull spermatozoa.